Investigating The Moderating Effect Of Social Media On The Relationship Between Brand Architecture And Brand Love Among Telecommunication Service Provider Users - Al Amirul Eimer Ramdzan Ali; Asmaul Husna Haris Fadzilah; Syahrul Nizam Salam; Nur Aqilah Hazirah Mohd Anim; Muhammad Fairuz bin Jamil; Amalina Mursidi; Mohd Safwan Ramli (Azad University Journals Cloud, 2024)
Non-Indexed Publication